PERBEDAAN HASIL BELAJAR DAN MINAT SISWA MENGGUNAKAN MEDIA MACROMEDIA FLASH DAN MEDIA POWTOON PADA MATERI LARUTAN ELEKTROLIT DAN NON-ELEKTROLIT - Randini Dwi Fahira; Makharany Dalimunthe (JGK (Jurnal Guru Kita), 2023)
This study aims to identify differences in learning outcomes and interests of students who are taught using Macromedia Flash and Powtoon media for electrolyte and non-electrolyte solutions. The population of this study were all students of class X MIPA, totaling 3 classes. Sampling was done by purposive sampling. Data on student learning outcomes were examined for validity, difficulty, discriminating power, and reliability using an objective test instrument consisting of 20 questions. To measure student interest, the data used a questionnaire filled in by the observer. Pretest, posttest, and students' interest in the two experimental classes were determined based on normality test data and homogeneity test. In the Experimental Class I and Experimental Class II, it was found that the pretest, posttest, and students' interest in the two experimental classes were normally distributed and homogeneous. Next, a hypothesis test was carried out using a two-party Independent Sample T-Test. To test the first hypothesis, the results were sig. 0.024 (sig. <0.05) and to test the hypothesis II, the results were sig. 0.000 (sig. <0.05), which means that there is a significant difference in the learning outcomes and interests of students taught with Macromedia Flash Media using the Problem Based Learning model compared to the learning outcomes and interests of students taught with Powtoon Media using the Problem Based Learning model in the material electrolyte and non-electrolyte solutions.